PENGGUNAAN NEAR FIELD COMMUNICATION DALAM KEGIATAN STOCK OPNAME DI LIBRARY & KNOWLEDGE CENTER BINUS UNIVERSITY INTERNATIONAL - Subagja Budirahman; Erika Erika (Perpustakaan Nasional RI, 2019)
The library Knowledge Center (KLC) of Binus University conducts annual stock opname as one of its collection development activities. The stock opname process ini KLC uses an integrated application with the collection database system. The application system used for stock opname is a standalone application, a development of the library information system and teh created by the Binus University IT development. The sytem is a desktop application plugged into a computer device and integrated with hardware in the from RFID reader as RFID tag reader sensor installed in the collection. A descriptive research method was used in this research because it aimed to find out the reason for the use of application research sytem on smartphone based on NFC technology in the activities of stock opname in LKC. The activity of stock opname with an RFID system used by LKC can be combined with NFC technology on smartphone and can be applied to one of LKC activies namely stock opname that makes the process more practical.